2023
DOI: 10.3390/eng4010037
|View full text |Cite
|
Sign up to set email alerts
|

SECDFAN: A Cyber Threat Intelligence System for Discussion Forums Utilization

Abstract: Cyber Threat intelligence (CTI) systems offer new capabilities in the arsenal of information security experts, who can explore new sources of data that were partially exploited during the past decades. This paper deals with the exploitation of discussion forums as a source of raw data for a cyber threat intelligence process. Specifically, it analyzes the discussion forums’ characteristics and investigates their relationship with CTI. It proposes a semantic schema for the representation of data collected from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…On the other hand, Sakellariou et al [ 43 ] emphasized using discussion forums as the raw data source for CTI and suggested a semantic schema for organizing the gathered data. The paper introduces the SECDFAN system, a comprehensive method for generating CTI products by analyzing forum content.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Sakellariou et al [ 43 ] emphasized using discussion forums as the raw data source for CTI and suggested a semantic schema for organizing the gathered data. The paper introduces the SECDFAN system, a comprehensive method for generating CTI products by analyzing forum content.…”
Section: Resultsmentioning
confidence: 99%
“…The paper introduces the SECDFAN system, a comprehensive method for generating CTI products by analyzing forum content. Furthermore, a reference architecture was created systematically to address all CTI-related concerns, including product sharing and collaboration among security experts [ 43 ].…”
Section: Resultsmentioning
confidence: 99%